Methocel E4M: Preparation and properties as a vehicle for the ocular drug delivery of vancomycin - Anutra Khangtragool (2018)
In this study, hydroxypropyl methylcellulose (HPMC, Methocel™ E4M) was chosen in 0.3% and 0.4% w/v concentrations at pH 7.1 as an ocular drug delivery vehicle for vancomycin and its in vitro characteristics and stability determined. The viscosity, osmolality, clarity, pH and contamination of each of the formulations were determined. From stability assessments, Methocel™ E4M 0.3% and 0.4% w/v pH 7.1 could be stored at 2-8°C and 30°C for 360 days. Osmolalities and pH were acceptable for use in the eyes. No contamination was found in both 0.3% and 0.4% w/v Methocel™ E4M pH 7.1. All solutions remained clear throughout the study. The kinematic viscosity of Methocel™ E4M 0.3% w/v relative to artificial tears indicated that it was suitable for the ocular drug delivery of vancomycin 50 mg/ml.